Detecting water in aviation honeycomb structures: the quantitative approach - Vavilov V. P. Vladimir Platonovich (2004, 2004)
Infrared thermographic inspection of water in aviation honeycomb panels is a wellknown technique. The hidden water can be detected due to its high thermal capacity that makes temperatures changes slow. A transient thermal regime can be realized by using external heaters or natural heating by the ambient. The paper describes some quantitative aspects of the water detection problem. The presented simulation results have been obtained by analyzing a one-dimensional model of a multi-layer plate where the ice-to-water phase transformation takes place. Some experimental results of inspecting Russian airplanes are also presented.